Association Between Consumption of Fruits and Vegetables and Risk of Colorectal Adenoma: A PRISMA-Compliant Meta-Analysis of Observational Studies. Issue 42 (October 2015) - Ben, Qiwen; Zhong, Jie; Liu, Jun; Wang, Lifu; Sun, Yunwei; Yv, Lifen; Yuan, Yaozong
Abstract : Abstract: There have been contradictory results about the association of fruits and vegetables intake with colorectal adenoma (CRA) risk, the precursor lesion of colorectal cancer. Herein, we have conducted a meta-analysis of the published observational studies to have a clear understanding about this association. Eligible studies up to November 30, 2014, were identified and retrieved by searching MEDLINE and EMBASE databases along with the manual review of the reference list of the retrieved studies. The quality of the included studies was evaluated using Newcastle-Ottawa Quality Assessment Scale, and random-effects model was used to calculate summary relative risk (SRR) and corresponding 95% confidence interval (CI). A total of 22 studies involving 11, 696 CRA subjects were part of this meta-analysis. The SRR for the highest versus the lowest intake of vegetables alone was 0.91 (95% CI: 0.80–1.02, P heterogeneity = 0.025), whereas for vegetables and fruits combined, it was 0.82 (95% CI: 0.75–0.91, P heterogeneity = 0.369), and for fruits alone, it was 0.79 (95% CI: 0.71–0.88, P heterogeneity = 0.111). In addition, linear dose–response analysis also showed similar results, for example, for per 100 g/d increment of fruits, the SRR was 0.94 (95% CI: 0.92–0.97) and for vegetables it was 0.98 (95% CI: 0.96–1.01). Nonlinear association was only observed for vegetables ( P nonlinearity = 0.024), but not for fruits ( P nonlinearity = 0.583). Thus, this meta-analysis suggested that fruits consumption have a significant protective effect on CRA risk, but not vegetables. Moreover, we recommend additional studies with prospective designs that use validated questionnaires and control for important confounders to further validate the overall results.